Excitation functions of the proton-induced nuclear reactions on Sn-nat up to 40 MeV - Khandaker, Mayeen Uddin; Lee, Y.O.; Kim, K.; Kim, K.S.; Lee, M.; Lee, Y.S.; Kim, G.; Cho, Y.S. (Elsevier, 2009)
We have measured the production cross-sections of the residual radionuclides for proton-induced reactions on natural tin by using a stacked-foil activation technique in the energy range from threshold energy to 40 MeV at the MC-50 cyclotron of the Korea Institute of Radiological and Medical Sciences. The results were compared with the earlier reported experimental data and theoretical calculations based on the TALYS and the ALICE-IPPE codes. The present results are in general good agreement with the available literature data and calculated results by using the computer codes TALYS and ALICE-IPPE. The thick target integral yields were also deduced from the measured excitation functions of the produced radionuclides. (C) 2008 Elsevier B.V. All rights reserved.